Great Economists and the Evolution of Economic Liberalism How Philosophy Has Helped Shape Economics - de Haan, Peter (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
XVII, 339 p. 6 illus., 5 illus. in color.